2017
DOI: 10.18280/ijht.350117
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation research on the micro effect mechanism of interfacial properties of nano SiO2/meta-aramid fiber

Abstract: In this paper, the molecular dynamics simulation was used to research the micro mechanism of nano SiO2 improving the properties of poly-m-phenyleneisophthalamide (MPIA) insulation paper in oil-immersed power transformers. For the first time, the double-layer model, with silica located at the bottom layer and poly-m-phenyleneisophthalamide fibre located at the upper layer, was built in the molecular simulation software. A strong interaction between SiO2 and meta-aramid was observed, and the interaction energy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
(16 reference statements)
0
16
0
Order By: Relevance
“…A model of a cluster made of nano-SiO 2 particles was created using the Materials Studio 5.0 Building Tool software (version) package [18] as shown in Figure 1. After drawing the cluster, hydrogen atoms were added to the unsaturated bonds.…”
Section: Methodsmentioning
confidence: 99%
“…A model of a cluster made of nano-SiO 2 particles was created using the Materials Studio 5.0 Building Tool software (version) package [18] as shown in Figure 1. After drawing the cluster, hydrogen atoms were added to the unsaturated bonds.…”
Section: Methodsmentioning
confidence: 99%
“…Crystallinity increases as well, consequently to the diffusion of the short chain segments towards the existing crystalline lamellae. It is well known that chain scissions are responsible for the loss of mechanical properties, while crystallinity makes the material more brittle and stiffer [15][16], [20].…”
Section: Discussionmentioning
confidence: 99%
“…Ageing is mainly due to polymer chain degradation, characterized by the oxidation of the macromolecules accompanied by morphological changes [13][14][15]. As such, FTIR spectroscopy can be regarded as a powerful technique to identify the different oxidation products developing during ageing and allowing also to quantify their concentration changes upon time.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that, the samples for direct shear test was quite difficult to be obtained from tunnel site due to rock fractures, shock and vibration during boring, especially for early-aged samples [15]. To assess the interfacial shear properties between rock and early-aged shotcrete, the bond interfaces of the samples should be prepared without being damaged, and making individual samples might be the possible way, like the direct shear tests on rock-concrete interface [16][17][18][19]. Given this comprehension, a new direct shear test method was developed through making individual samples, without coring process after shotcreting.…”
Section: Introductionmentioning
confidence: 99%